Effect of Rubber Mixing Sequence Variation Upon Bound Rubber Formation and Its Physical Properties - Hasan, Abu; Rochmadi; Sulistyo, Hary; Honggokusumo, Suharto (Asian Journal of Chemistry, 2013)
This study examined the effect of mastication and the addition sequence of rubber chemicals and filler during the mixing process on the formation of bound rubber and the physical properties of the natural rubber vulcanizates. An analysis of the curing characteristics, rubber bound formation and physical properties of vulcanizates were carried out on a natural rubber formula that had been masticated and mixing, followed by curing. Two methods of mastication were used and each mastication process was followed by four different mixing sequences. In the first mastication method, rubber was masticated for 5 min, which was followed by the simultaneous addition of rubber chemicals and carbon black N 330. In the second method, rubber was masticated for 3 min and carbon black and rubber chemicals were added subsequently. The addition of rubber chemicals and carbon black into the masticated rubber was distinguished by the sequence and time allocated for each mixing process. Carbon black was added into two stages. In the first stage, 10 phr was added first and the remaining 40 phr was added later along with oil. In the other methods, carbon black was added in the first and second stage at the following ratios: 20:30, 30:20 and 40:10. The second method formed more strongly bound rubber with superior physical properties than that of the first method. The difference in those results was attributed to the mastication time. The softness of the masticated rubber produced increased with increasing mastication time. This means that softer masticated rubber possessed a low shearing force to break the carbon black aggregates and produced a poor dispersion in the rubber. Therefore, less bound rubber was formed. The second method, which was 40:10, gave the best results. More carbon black mixed in the first stage without the addition of processing oil and rubber chemicals gave rise to a better dispersion than when less carbon black was mixed.